Bacterial profile and antibiotic susceptibility pattern of adult lower respiratory tract infections in Colombo, Sri Lanka - Nadeesha Amarasinghe; Muthulingam Athavan; Deepal Jayamanne; Yamuna Rajapakshe; Aflah Sadikeen; Kirthi Gunasekara; Amitha Fernando; Lilani Karunanayake (Journal of Health and Social Sciences)
Introduction: Lower respiratory tract infections (LRTIs) remain the deadliest communicable disease around the world. This study was conducted to identify the bacterial etiology of LRTIs among patients who attended the Central Chest Clinic in city of Colombo, Sri Lanka and their antibiotic susceptibility profile to enable clinicians to take decisions on effective empirical antibiotics. Methods: Sputum samples were collected from 1,372 patients over the age of 18 years with suspected LRTIs during the year 2015. The samples were collected and processed according to standard laboratory procedures at the microbiology laboratory of the Medical Research Institute of Sri Lanka. Results: Most of reports (58%) were from patients diagnosed with infective exacerbations of chronic lung diseases. Out of all sputum cultures processed, 404 (29.4%) resulted positive for pathogenic bacterial organisms. Coliforms (n = 176, 43.6%), and Pseudomonas aeruginosa (n = 117, 29%) were the most common isolated bacteria, followed by Moraxella (n = 47, 11.6%), Haemophilus influenzae (n = 23, 5.7%), and Streptococcus pneumoniae (n = 18, 4.4%). The two most common bacteria isolated showed a high sensitivity for co-amoxyclav, quinolones, 3rd generation cephalosporins, carbapenems and aminoglycosides, while coliforms were highly resistant (98%) to ampicillin. S. pneumoniae showed a high resistance for penicillin (67%) and erythromycin (61%), while Haemophilus showed a good sensitivity to co-amoxyclav (96%). There was no significant correlation between rainfall and proportions of coliforms (r = - 0.152, P = 0.638) and Pseudomonas (r = 0.271, P = 0.395) during the year. Discussion and Conclusion: In our study, the most predominant pathogens recovered from LRTIs were P. aeruginosa and coliforms (Klebsiella spp.) as Gram negative, and S. pneumoniae as Gram positive bacteria. Co-amoxyclav, 3rd generation cephalosporins, quinolones and all second line antibiotics tested were the most efficient antibiotics in treatment of LRTIs, differently from ampicillin, erythromycin and penicillin that were not efficient antibiotics in treating this disease in our locality.